FEATURES OF THE CLINICAL COURSE OF ROTAVIRUS INFECTION IN CHILDREN INFECTED WITH HERPES VIRUSES AND THEIR BLOOD INTERLEUKIN REACTIONS - Sliepchenko, Margaryta (Inter Collegas, 2019)
FEATURES OF THE CLINICAL COURSE OF ROTAVIRUS INFECTION IN CHILDREN INFECTED WITH HERPES VIRUSES AND THEIR BLOOD INTERLEUKIN REACTIONS Sliepchenko M.Yu. Background. The widespread prevalence of intestinal infections of rotavirus etiology, the economic damage caused by it and the difficulties of treating patients cause the medical and social significance of this pathology. Along with this, a herpes virus infection and its negative effect on the immune response of the human body is a pressing problem. The purpose of the study is to identify the characteristics of presentation and the course of rotavirus infection in children infected with herpes viruses, and to establish the characteristics of the reaction of interleukins in their blood. Subjects and Methods. 38 children aged one to three years with moderate and severe forms of intestinal infection rotavirus etiology, who received appropriate treatment were examined. The children were divided into two groups: Group 1 included 18 children who did not have a background infection and Group 2 comprised 20 patients with acute rotavirus infection who were infected with herpes viruses. Along with the generally accepted clinical and laboratory examination, the levels of interleukins 1β, 4, TNFα in the blood serum in the time course of the disease were determined by an ELISA method for all children. Results. Assessment of clinical and immunological parameters of rotavirus infection in children showed that infection with viruses of the herpes group contributed to a less severity of symptoms of the disease at the initial stage, but longer persistence, which was probably due to insufficient reaction of proinflammatory interleukins in blood in the acute period at relatively high levels during the course of the disease. Keywords: clinic, children, cytokines, herpes and rotavirus infections.